Relationship between the academic and socio-economic profile of the entrants with the academic performance at university and the beliefs of control and self-efficacy for learning - García Ampudia, Lupe (2003)
The present investigation faced the access problem the data of the academic record and socioeconomic previous of the entrant, reason by which it was done without the variables of academic profile and socioeconomic and it was concentrated in the other variables, is so in the present work it studies the beliefs of control and self- efficacy for the learning and the yield in his relation with the academic yield of the students of the Greater National University of San Marcos, pertaining to five areas of study. The sample was constituted by 1010 entrants students basic year 2001 to the health areas, sciences, economic-enterprise humanities, engineering and; the used instruments were the scale of control beliefs and autoeficacia for the learning of the «questionnaire of learning strategies and motivation» (CEAM). The results show to scores higher of beliefs of average control and self- efficacy for the learning that in self-efficacy for the yield, appear significant relations in self- efficacy for the yield and academic yield, as weIl as with the areas of study of the students, as far as the beliefs of control and self-efficacy for the learning was not relation with the academic yield and in the comparison of this one variable with groups with different level from academic yield were not either differences; in the comparison by study areas if were significant differences.